CULTURE, MEMORY, AND TECHNOLOGY. - Billington, James H. (Sewanee Review)
Discusses the role of technology in the preservation of historical records. Reasons for the preservation; Effect of television on culture; Efforts of the United States Library of Congress to bring the historical archives of the U.S. and other countries into the Internet through the American Memory online service; Need to integrate electronic technology into books.